Improvement of the grapevine variety ‘Kadarka’ by the selection of new clones - Werner, J.; Kozma, P. (International Journal of Horticultural Science, 2013)
Red wine culture in Hungary was developed due to the grapevine variety ‘Kadarka’, originated from the Balkans, from the 16th and 17th centuries. ‘Kadarka’ was the first grapevine variety cultivated on the largest area in Hungary until the 1950’s, but its production area has been reduced significantly in the past decades. In the period of Hungarian grapevine reconstruction (from the 1960’s), the selection of the grapevine varieties and clones was determined by the system of cultivation (large growing space, large load and mechanized technology) that was based on the aspects of quantity. It did not promote the majority of the autochton and regional grapevine varieties to remain competitive. ‘Kadarka’ is a grapevine variety having an extraordinary variability in forms; however, a considerable part of its old stocks has disappeared. Nowadays, only two of its high yield clones are cultivated. ‘Kadarka’ becomes more differentiated from other, red wine producing, grapevine varieties, more preferred and newly requested by the fine aroma, spice, unique harmony of its wine less rich in tannin. The new market and environmental challenges in the field of wine production necessitate the preservation and improvement of the biological basis. In 2001 the Institute of Viticulture and Enology Pécs analyzed an old stock having a variability in forms in order to preserve the development and variability of the biological basis of ‘Kadarka’. Clones of great biological value were selected from it, with which the quality and yield security of ‘Kadarka’ can be increased. In 2010 and in 2012, six clones were submitted for state approval.